2022
DOI: 10.3390/gels8070424
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Mechanical, Conductive, and Cryophylactic Double Network Hydrogel for Flexible and Low-Temperature Tolerant Strain Sensors

Abstract: Due to their stretchability, conductivity, and good biocompatibility, hydrogels have been recognized as potential materials for flexible sensors. However, it is still challenging for hydrogels to meet the conductivity, mechanical strength, and freeze-resistant requirements in practice. In this study, a chitosan-poly (acrylic acid-co-acrylamide) double network (DN) hydrogel was prepared by immersing the chitosan-poly (acrylic acid-co-acrylamide) composite hydrogel into Fe2(SO4)3 solution. Due to the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Then, Young’s modulus can be obtained from Equation (1). Tensile testing experiments have been carried out to address the mechanical properties of biodegradable cornstarch- [ 112 ], starch/dolomite- [ 113 ] or lignocellulosic- [ 114 , 115 ] based polymers, hydrogels made by carbon dots, hydroxyapatite and polyvinyl acetate [ 116 ] or chitosan-poly (acrylic acid-co-acrylamide) double network [ 117 ], natural-rubber-modified flame-retardant organic montmorillonite [ 118 ] or chlorhexidine-loaded poly (amido amine) [ 119 ] dendrimers, blends consisting of fibrillar polypropylene and polyethylene terephthalate [ 120 ] or poly ε-caprolactone/poly-(lactide-co-ε-caprolactone (PLCL) [ 121 ], polyurethane [ 122 ] and polyethylene [ 123 ] foams, organosilicone elastomer liquid crystals [ 124 ], and skeletal muscle tissues [ 125 ] or PLCL layered sheets with mesenchymal stem cells [ 126 ].…”
Section: Figurementioning
confidence: 99%
“…Then, Young’s modulus can be obtained from Equation (1). Tensile testing experiments have been carried out to address the mechanical properties of biodegradable cornstarch- [ 112 ], starch/dolomite- [ 113 ] or lignocellulosic- [ 114 , 115 ] based polymers, hydrogels made by carbon dots, hydroxyapatite and polyvinyl acetate [ 116 ] or chitosan-poly (acrylic acid-co-acrylamide) double network [ 117 ], natural-rubber-modified flame-retardant organic montmorillonite [ 118 ] or chlorhexidine-loaded poly (amido amine) [ 119 ] dendrimers, blends consisting of fibrillar polypropylene and polyethylene terephthalate [ 120 ] or poly ε-caprolactone/poly-(lactide-co-ε-caprolactone (PLCL) [ 121 ], polyurethane [ 122 ] and polyethylene [ 123 ] foams, organosilicone elastomer liquid crystals [ 124 ], and skeletal muscle tissues [ 125 ] or PLCL layered sheets with mesenchymal stem cells [ 126 ].…”
Section: Figurementioning
confidence: 99%
“…Recently, dual network (DN) hydrogels, first established in 2003 by Gong et al , 14 have been recently demonstrated to be effective in constructing flexible sensors possessing enhanced physicochemical properties and integrated multifunctionality. 15–18 For example, Li et al fabricated a tough DN hydrogel through combining thermoreversible κ-carrageenan hydrogel with polyacrylamide network, where the former rendered good recoverability and self-healing capability to the DN hydrogel while the latter enabled 3D printing by means of UV light-triggered photopolymerization. 19 Gu et al employed the host–guest interaction and dynamic covalent bond to prepare DN hydrogels, acquiring satisfactory comprehensive performance including stretchability, strength, remodeling ability, self-healing property, self-adhesiveness, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…An effective method to improve the freezing resistance of hydrogel is to permeate organic solvents [ 19 ]. Inspired by the oil-water system, Rong et al [ 20 ] reported an antifreezing conductive organic hydrogel using H 2 O/Ethylene (Eg) dual solvent as the dispersion medium.…”
Section: Introductionmentioning
confidence: 99%